Determination of stature from foot lengm With reference to malay population - Mohamed, Khairulmazidah (Universiti Sains Malaysia, 2006)
Foot impression evidence are often found at the crime scene during the commission of offences like burglary, robbery, and even in murder cases an so on. Although this type of impression is occasionally found at the scene when compared to shoe impression evidence, criminals tend to remove their footwear while committing crime in order to avoid noise while walking, to have better grip in climbing walls, and comfortable for fast escaping. In Asian countries, in many places people tend to walk in barefoot. A lot of information can be obtained from foot impression evidence. This evidence can be used as a positive evidence in many crime scenes. This is because of the uniqueness of footprint in terms of the ridge characteristic on the sole as well as the shape of the foot from various dimensions. The length of the foot is a valuable factor to identify the height of the person who committed the offence. Estimation of stature from the dimensions of foot or shoeprints has considerable value in forensic investigation as to develop descriptions from evidence at the crime scene and in corroborating height estimates from witnesses. In this study, the regression equation of stature estimation from foot length is derived using the simple linear regression statistical method from 107 subjects. The population is represented Malay population from various districts and states in Malaysia. The fonnulae derived have been recorded.